Myeloid-specific blockade of notch signaling alleviates dopaminergic neurodegeneration in Parkinson’s disease by dominantly regulating resident microglia activation through NF-κB signaling - Liang, Shi-Qian; Li, Peng-Hui; Hu, Yi-Yang; Zhao, Jun-Long; Shao, Fang-Ze; Kuang, Fang; Ren, Kai-Xi; Wei, Tiao-Xia; Fan, Fan; Feng, Lei; Han, Hua; Qin, Hong-Yan (Frontiers in Immunology, 2023)
Yolk sac-derived microglia and peripheral monocyte-derived macrophages play a key role during Parkinson's disease (PD) progression. However, the regulatory mechanism of microglia/macrophage activation and function in PD pathogenesis remains unclear.Recombination signal-binding protein J (RBP-J)-mediated Notch signalling regulates macrophage development and activation. In this study, with an MPTP hydrochlorideinduced acute murine PD model, we found that Notch signalling was activated in amoeboid microglia accompanied by a decrease in tyrosine hydroxylase (TH) positive neurons. Furthermore, using myeloid-specific RBP-J knockout (RBP-J cKO ) mice combined with a PD model, our results showed that myeloid-specific disruption of RBP-J alleviated dopaminergic neurodegeneration and improved locomotor activity.FACS analysis showed that the number of infiltrated inflammatory macrophages and activated MHC II + microglia decreased in RBP-J cKO mice compared with control mice. Moreover, to block monocyte recruitment by using CCR2 knockout mice, the effect of RBP-J deficiency on dopaminergic neurodegeneration was not affected, indicating that Notch signalling might regulate neuroinflammation independent of CCR2 + monocyte infiltration. Notably, when microglia were depleted with the PLX5622 formulated diet, we found that myeloid-specific RBP-J knockout resulted in more TH + neurons and fewer activated microglia. Ex vitro experiments demonstrated that RBP-J deficiency in microglia might reduce inflammatory factor secretion, TH + neuron apoptosis and p65 nuclear translocation. Collectively, our study first revealed that RBP-J-mediated Notch signalling might participate in PD progression by mainly regulating microglia 3 activation through NF-B signalling.